2011
DOI: 10.1186/1475-925x-10-54
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure long term regulation: A neural network model of the set point development

Abstract: BackgroundThe notion of the nucleus tractus solitarius (NTS) as a comparator evaluating the error signal between its rostral neural structures (RNS) and the cardiovascular receptor afferents into it has been recently presented. From this perspective, stress can cause hypertension via set point changes, so offering an answer to an old question. Even though the local blood flow to tissues is influenced by circulating vasoactive hormones and also by local factors, there is yet significant sympathetic control. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Included examples are blood pressure long-term regulation, oscillometric measurement of systolic and diastolic blood pressures, a procedure for the evaluation of non-invasive blood pressure simulators, neural set points for the control of arterial pressure, the estimation of mean arterial pressure from the oscillometric cuff pressure, and the feasibility of measuring coronary blood flow. 3136…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Included examples are blood pressure long-term regulation, oscillometric measurement of systolic and diastolic blood pressures, a procedure for the evaluation of non-invasive blood pressure simulators, neural set points for the control of arterial pressure, the estimation of mean arterial pressure from the oscillometric cuff pressure, and the feasibility of measuring coronary blood flow. 3136…”
Section: Resultsmentioning
confidence: 99%
“…Included examples are blood pressure long-term regulation, oscillometric measurement of systolic and diastolic blood pressures, a procedure for the evaluation of non-invasive blood pressure simulators, neural set points for the control of arterial pressure, the estimation of mean arterial pressure from the oscillometric cuff pressure, and the feasibility of measuring coronary blood flow. [31][32][33][34][35][36] The term "image" is mainly used in the context of guiding treatments. Some examples include image-guided oral implantology, design of the image-guided biopsy marking system for gastroscopy, extraction of three-dimensional (3D) information on bone remodeling in the proximity of titanium implants in SRmuCT image volumes, 3D patient-specific geometry of the muscles involved in knee motion from selected magnetic resonance imaging (MRI) images, and jaw tissues segmentation in dental 3D computed tomography (CT) images using fuzzy-connectedness and morphological processing.…”
Section: Cluster 1: Biomedicalmentioning
confidence: 99%
“…This suggests that VMH efferents within the NTS are not concerned with taste (Chen and Di Lorenzo, 2008), but instead contribute to autonomic and sympathetic functions. Specifically, caudal regions of the NTS are principally concerned with tonic autonomic regulation of blood pressure (Massari et al, 1998;Thrasher, 2004;Zanutto et al, 2011). Importantly, VMH activity has been shown to influence cardiovascular function.…”
Section: Projections Of Hypothalamic Sf1 Neuronsmentioning
confidence: 99%
“…Recent findings confirm that there is indeed a set-point for mean long-term BP that is regulated by the nervous system rather than the generally accepted model that the renal output curve determines the set-point for long-term arterial BP regulation. Osborn has provided compelling arguments for a central nervous system–based set-point for long-term arterial BP 56 and in recent articles by Zanuto et al, 57 , 58 it was shown that when all of the cardiovascular receptors (baro-, chemo-, and cardiopulmonary) are deinnervated, sustained hypertension results. Zanuto has also provided evidence that nucleus tractus solitarius acts as a compactor and controls the set-point for mean atrial BP, which is consistent with Pribram's model.…”
Section: Discussionmentioning
confidence: 99%